On the Subject of the Theory of Plot (‘Syuzhetologia’) - Силантьев, Игорь (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The paper discusses the main categories of narratological analysis, such as point of view, fact, event, narrative, plot and story, motif. It is shown that plot and story are opposed aspects of interpretation of a narrative. The necessary distinction between narratology and the theory of plot in terms of research subject is made.